Living kidney donation: a comparison of laparoscopic and conventional open operations. Issue 917 (1st March 2002) - Waller, J R; Hiley, A L; Mullin, E J; Veitch, P S; Nicholson, M L
Abstract : Laparoscopic donor nephrectomy has the potential to lessen the burden placed on live kidney donors. This study describes the first British comparison of donor morbidity and recovery following conventional open donor nephrectomy (ODN) and laparoscopic donor nephrectomy (LDN). An initial series of LDN (n=20) was compared to a historical control group of ODN (n=34). Laparoscopic operations were performed via a transperitoneal approach, the kidney being removed through a 6–12 cm Pfannensteil incision. Open operations were performed using a retroperitoneal flank approach with resection of the 12th rib. Postoperatively, donors were managed with a patient controlled analgesia system. LDN was associated with shorter mean (SD) inpatient stay (6 (2) v 4 (1) days; p=0.0001) and lower parenteral narcotic requirements (morphine 179 (108) v 67 (54) mg; p=0.0001). Laparoscopic donors started driving their cars sooner (2 (1.5) v 6 (4) weeks; p=0.0001) and returned to work more quickly (5 (3) v 12 (6) weeks; p=0.0001) than open nephrectomy donors. There were no differences in recipient serum creatinine levels at three months post-transplant but two recipients of transplant kidneys retrieved laparoscopically (10%) developed ureteric obstruction, whereas this complication did not occur after ODN (p=0.13). LDN is associated with less postoperative pain and a substantial improvement in donor recovery times. It is not yet clear whether or not the outcome of the recipient kidney transplants are the same after ODN and LDN and much more experience is required before the place of this new technique can be defined.